9 Performance of Indonesian Ministry of Health in Overcoming Hoax About Vaccination Amid the COVID-19 Pandemic on Social Media - Daniel Susilo; Teguh Dwi Putranto; Charles Julian Santos Navarro (Faculty of Social and Political Science, Universitas Muhammadiyah Tangerang, 2021)
The coronavirus disease (COVID-19) pandemic in early 2021 is still a “big disaster” for Indonesia. The public is increasingly confused about the Government’s Vaccination program in reducing the number of COVID-19 cases in Indonesia. The development of Vaccine-related hoaxes such as safe or not, halal or not, has also become a new job faced by the Government, especially the Ministry of Health. This study aims to determine the Indonesian Ministry of Health’s performance in overcoming hoaxes against Vaccinations during the Covid-19 pandemic. The method used in this research is Krippendorff content analysis on Instagram posts of the Ministry of Health @kemenkes_ri during the period 1 January 2021 to 29 January 2021. The conclusion obtained in this study is that the Ministry of Health’s efforts in dealing with hoaxes circulating in the community regarding the Covid-19 Vaccination are by presenting health experts in providing information related to the Covid-19 Vaccine. The information conveyed is related to the quality and safety of Vaccines, to the Vaccine development process.Keywords: Performance, social media, hoax, vaccination, COVID-19 ABSTRAKPandemi penyakit coronavirus (COVID-19) di awal tahun 2021 masih menjadi “bencana besar” bagi Indonesia. Masyarakat semakin bingung dengan program vaksinasi yang dilakukan Pemerintah dalam menekan angka kasus COVID-19 di Indonesia. Berkembangnya hoaks terkait vaksin seperti aman atau tidak, halal atau tidak, juga menjadi pekerjaan baru yang dihadapi Pemerintah, khususnya Kementerian Kesehatan. Penelitian ini bertujuan untuk mengetahui kinerja Kementerian Kesehatan RI dalam mengatasi hoaks terhadap vaksinasi selama pandemi Covid-19. Metode yang digunakan dalam penelitian ini adalah analisis konten Krippendorff pada postingan Instagram Kementerian Kesehatan @kemenkes_ri selama periode 1 Januari 2021 hingga 29 Januari 2021. Kesimpulan yang diperoleh dalam penelitian ini adalah bahwa upaya yang dilakukan oleh Kementerian Kesehatan dalam menghadapi hoaks yang beredar di masyarakat terkait vaksinasi Covid-19 adalah dengan menghadirkan pakar kesehatan dalam memberikan informasi terkait vaksin Covid-19. Informasi yang disampaikan terkait dengan kualitas dan keamanan vaksin, hingga proses pengembangan vaksin. Kata Kunci: Kinerja, media sosial, hoaks, vaksinasi, COVID-19